chopenhauer e os Upanishads: vontade e representação na tradição indiana - Veras, Roberto Pereira (2015)
This research tends to explicit the synthetic manner of a philosophical trajectory about Arthur Schopenhauer´s theory (1788-1860) with the sacred philosophy of hinduism. Furthermore, we will analyze in a conceptual hermeneutic form of the thon I and II of his maximum work the world as will and representation from 1819, as for Upanishads: Isha, Kena e Mundaka. In addition to it, we will conceive which elements and tendencies propose to the philosopher from Danzig the authentic access to the oriental philosophy, as well for the existent relation in his thought that inexorably establish an analogy yet in his youth as a deforce element in his maximum thesis about the will. This way discoursing, we realize that the will acts in its many variety levels of objectivities, strutting the existence of things through the plurality of the states that result in uniqueness essence of the being while thing-into-it.